1997
DOI: 10.1038/hdy.1997.142
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of seed dormancy in Arabidopsis using recombinant inbred lines and MQM mapping

Abstract: The genetic differences for seed germination between two commonly used Arabidopsis thaliana ecotypes Ler and Col, both showing a low level of seed dormancy, were investigated. The analysis was performed with 98 recombinant inbred lines (RILs) derived from the cross between the two ecotypes, and these lines had previously been analysed for molecular marker composition by Lister and Dean (Norwich, UK). The analysis of germination was performed on seeds grown in three different maternal environments and each seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…We determined that the RILs used in this work (Lister and Dean, 1993) show moderate variability in their germination rates in 250 mm NaCl. These results agree with those obtained by Van der Schaar et al (1997), who studied seed dormancy in these RILs, also finding a moderate variability. We found very small differences between the parental accessions (Col-4 and Ler-0) in their germination rates determined 15 d after sowing on 250 mm NaCl, in contrast with the significant differences observed between both wild-type strains in morphological features such as bearing, silique size, or flowering time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We determined that the RILs used in this work (Lister and Dean, 1993) show moderate variability in their germination rates in 250 mm NaCl. These results agree with those obtained by Van der Schaar et al (1997), who studied seed dormancy in these RILs, also finding a moderate variability. We found very small differences between the parental accessions (Col-4 and Ler-0) in their germination rates determined 15 d after sowing on 250 mm NaCl, in contrast with the significant differences observed between both wild-type strains in morphological features such as bearing, silique size, or flowering time.…”
Section: Discussionsupporting
confidence: 92%
“…In the last two cases, the genes at the QTL detected have been cloned, which demonstrates that the QTL approach not only gives a relatively wide genome interval but also facilitates the identification of the genes responsible for the trait under study. In Arabidopsis, QTL have been identified that control seed dormancy (Van der Schaar et al, 1997), seed size (Alonso-Blanco et al, 1999), seed soluble oligosaccharides and storability (Bentsink et al, 2000), and flowering time (Kowalski et al, 1994;Clarke et al, 1995;Alonso-Blanco et al, 1998;Juenger et al, 2000). The cloning of the CRY2 gene of Arabidopsis, encoding the blue-light receptor cryptochrome 2, using a QTL approach has recently been reported (El-Assal et al, 2001).…”
mentioning
confidence: 99%
“…The latter is the basis of multiple QTL mapping (MQM) approach (Jansen 1993, Jansen and or composite interval mapping (Zeng 1993). Those two strategies were combined in a study by Van der Schaar et al (1997) in Arabidopsis with the result that CIs have been reduced and more QTL than normal have been identified. However, CIs were not reduced to much less than 10 cM, and then only for the QTL with the largest effects.…”
Section: Limiting Factors Of the Approaches: A Single Approach Is Notmentioning
confidence: 99%
“…Many dormancy QTLs have been identified from model plants and major cereal crops. For example, dormancy QTLs are distributed over all five chromosomes (chr) in Arabidopsis (Arabidopsis thaliana) ( Van der Schaar et al, 1997;Alonso-Blanco et al, 2003;Clerkx et al, 2004) and 11 of the 12 chr in cultivated (Oryza sativa) (Wan et al, 1997;Lin et al, 1998;Dong et al, 2002;Miura et al, 2002), wild (O. rufipogon) (Cai and Morishima, 2000;Thomson et al, 2003), and weedy (O. sativa) (Gu et al, 2004) rice. Dormancy QTLs in barley (Oberthur et al, 1995;Li et al, 2003;Prada et al, 2004), sorghum (Lijavetzky et al, 2000), and wheat (Anderson et al, 1993;Kato et al, 2001;Mares and Mrva, 2001;Groos et al, 2002;Osa et al, 2003;Kulwal et al, 2004) have been identified to seek gene resources to impart resistance to preharvest sprouting (PHS) and to manipulate germination programs in the malting process.…”
Section: Introductionmentioning
confidence: 99%